1999
DOI: 10.3354/dao035081
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and dynamics of shell disease in the edible crab Cancer pagurus:a preliminary study of Langland Bay, Swansea, UK

Abstract: The prevalence and severity of shell disease in the edible crab Cancer pagurus (L.) was investigated in animals collected from Langland Bay, Gower, South Wales, UK, at monthly intervals from 1997 to 1998. Shell disease is the progressive degradation of exoskeletal chitin accompanied by melanisation of the affected region. Over 50% of the crabs sampled had 1 or more black-spot lesions. The proportion of exoskeleton affected increased with the size of the crab. Male crabs showed significantly higher levels of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 19 publications
4
48
1
Order By: Relevance
“…1a). Such lesions have previously been shown to occur on all regions of the exoskeleton (Vogan et al, 1999). SEM examination of these lesions revealed the extensive nature of the cuticular erosion into the chitinous procuticle ( Fig.…”
Section: Bacterial Diversity In Shell Disease Lesions and Diseased Crabsmentioning
confidence: 83%
See 2 more Smart Citations
“…1a). Such lesions have previously been shown to occur on all regions of the exoskeleton (Vogan et al, 1999). SEM examination of these lesions revealed the extensive nature of the cuticular erosion into the chitinous procuticle ( Fig.…”
Section: Bacterial Diversity In Shell Disease Lesions and Diseased Crabsmentioning
confidence: 83%
“…Smolowitz et al, 1992) or (ii) as a result of septicaemic infections by pathogenic bacteria originating by entry through the lesion sites (Baross & Tester, 1978 ;Vogan et al, 2001). Previous studies have found high prevalences of shell disease in the commercially fished edible crab, Cancer pagurus, from the Swansea Bay region of South Wales (Vogan et al, 1999). The current study investigates the pathogenic effects of a number of exoskeletal chitinolytic isolates both in terms of their abilities to degrade cuticular chitin (i.e.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, high incidence of shell disease can be important in shedding systems because the causative pathogens are contagious (Sandifer & Eldridge 1974, Sindermann 1989. Fortunately for shedding facilities, if a crab successfully molts, it will shed any shell disease and will have a clean, soft shell that is appetizing and marketable (Vogan et al 1999). …”
Section: Discussion Prevalence and Intensity Of Shell Diseasementioning
confidence: 99%
“…Ultimately the crab may die either from septicaemia (if the damaged cuticle is breached and these or other bacteria gain entry to the open haemocoele: Vogan et al 2001) or from an inability of such individuals to withdraw from the shell at ecdysis (Fisher et al 1978). Vogan et al (1999) showed an unusually high prevalence (ca. 55%) of shell disease in Cancer pagurus populations in Langland Bay near Swansea sampled in 1997-98.…”
Section: Introductionmentioning
confidence: 99%